A practical guide to decontamination in healthcare - McDonnell, Gerald E.; Sheard, Denise (Hoboken : John Wiley & Sons, 2012)
Prevention is the first line of defence in the fight against infection. As antibiotics and other antimicrobials encounter increasing reports of microbial resistance, the field of decontamination science is undergoing a major revival. A Practical Guide to Decontaminationin Healthcare is a comprehensive training manual, providing practical guidance on all aspects of decontamination including: microbiology and infection control; regulations and standards; containment, transportation, handling, cleaning, disinfection and sterilization of patient used devices; surgical instrumentation; endoscopes.
Microorganisms are everywhereSources of contamination; The role of infection prevention and control; Infection control and prevention strategies; Reprocessing role in infection control and prevention; 6 Chemistry and physics; Introduction; Solids, liquids, gases and plasmas; Mixtures, formulations and solutions; Weights, measures and other physical considerations; The pH scale: defining acids and bases; Other common chemical measurement methods; An introduction to sampling; Titration; Conductivity; Total dissolved solids; Total organic carbon; Inductively coupled plasma mass spectrometry.
Light, radiation and the electromagnetic spectrum.
Includes bibliographical references and index.
Print version record.
Keywords: Infection -- Prevention; Hospital buildings -- Disinfection; Disinfection and disinfectants; Sterilization; MEDICAL -- Epidemiology; MEDICAL -- Health Risk Assessment; Disinfection and disinfectants; Hospital buildings -- Disinfection; Infection -- Prevention; Sterilization; Electronic books